2006
DOI: 10.1021/jf052183k
|View full text |Cite
|
Sign up to set email alerts
|

Codon Optimization ofCandida rugosa lip1 Gene for Improving Expression inPichia pastorisand Biochemical Characterization of the Purified Recombinant LIP1 Lipase

Abstract: An important industrial enzyme, Candida rugosa lipase (CRL) possesses several different isoforms encoded by the lip gene family (lip1-lip7), in which the recombinant LIP1 is the major form of the CRL multigene family. Previously, 19 of the nonuniversal serine codons (CTG) of the lip1 gene hav been successfully converted into universal serine codons (TCT) by overlap extension PCR-based multiple-site-directed mutagenesis to express an active recombinant LIP1 in the yeast Pichia pastoris. To improve the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 25 publications
5
66
0
Order By: Relevance
“…The enzyme lipase contains several positively charged surface exposed amino acids, i.e., histidine, lysine, and arginine amino acids through its sequence. The sequence, as well the amino acid distribution in the tertiary structure of lipase is well known [34][35][36]. The presence of these amino acid residues on the surface of lipase was considered important to plan an immobilization procedure involving these positively charged amino acid residues.…”
Section: Immobilization Of Lipasementioning
confidence: 99%
“…The enzyme lipase contains several positively charged surface exposed amino acids, i.e., histidine, lysine, and arginine amino acids through its sequence. The sequence, as well the amino acid distribution in the tertiary structure of lipase is well known [34][35][36]. The presence of these amino acid residues on the surface of lipase was considered important to plan an immobilization procedure involving these positively charged amino acid residues.…”
Section: Immobilization Of Lipasementioning
confidence: 99%
“…It was reported that 25 of the total 61 yeast codons were optimal, whereas in Pichia, Zhao et al (2000) validated 19 optimal expression codons by analyzing the usage of 28 synonymous codons. Many researchers have managed to optimize these codons in Pichia to improve the expression of heterologous genes (Outchkourov et al, 2002;Hu et al, 2006;Chang et al, 2006;Li et al, 2008;Shumiao et al, 2010;Gao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported significant improvements in the expression of foreign genes in yeast by codon optimization (Outchkourov et al, 2002;Chang et al, 2006;Hu et al, 2006;Li et al, 2008;Shumiao et al, 2010;Bai et al, 2011;Gao et al, 2012). The significantly higher protein yields in the native folded state, higher purity, and improved function establish the value of the gene codon optimization approach.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the codon bias of S. cerevisiae and P. pastoris, serine-encoding codons and the 5'-UTR region of the C. rugosa lipase gene were optimized to make it achieve the effective expression in the two host cells. This greatly shortens the fermentative cycle [27,28]. Wei et al [29] optimized a thermostable α-amylase gene (pfa) sequence based on the Pichia codon bias and artificially synthesized it.…”
Section: Improving the Production Of Industrial Enzymes By Designing mentioning
confidence: 99%